Analysis of caesarean section rate according to modified Robson’s classification at tertiary care centre in Uttarakhand, India - Dogra, Kusum; Arora, Neetu; Sharma, Bhawna; Tanwar, Meenakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: High caesarean section rate worldwide including India is matter of concern. The aim of this study is to analyse caesarean section rate at tertiary care centre according to Modified Robson’s classification. Methods: This retrospective study was conducted at Shri Guru Ram Rai Institute of Medical and Health Sciences (SGRRIMHS) and Shri Mahant Indiresh Hospital at Dehradun from April 2018 to September 2018. All women delivered during this period were classified according to modified Robson’s classification using their maternal characteristics and obstetric history. For each group, authors calculated the caesarean section rate within the group and its contribution to overall caesarean section rate. Results: Out of total 1302 women delivered, 395 underwent CS (30.3%).The major contribution to overall caesarean section rate was 33.4% by group 5 (Previous CS, singleton, cephalic, >37weeks) followed by 16.7% by group 1 (nullipara, singleton, cephalic, >37 weeks, spontaneous labour), 12.4% by group 3 ( multipara, singleton, cephalic, >37 weeks, spontaneous labour ).CS rates among various group ranges from 100% among women with abnormal lie (group 9) to 77.5% in nulliparous breech (group 6), 73.7% in previous CS (group 5) and least 11.2% in multipara induced or pre labour CS (group 4). Conclusions: Modified Robson classification is simple, systematic, reproducible and can be effectively utilized in analyzing delivering women. Major contribution to overall caesarean section is made by previous CS.